CTNI-66. THE PREOPERATIVE BRAIN IRRADIATION IN GLIOBLASTOMA (POBIG) STUDY: A NOVEL TREATMENT PARADIGM TO IMPROVE OUTCOMES?. (14th November 2022) - Borst, Gerben; Waqar, Mueez; McBain, Catherine; Beasley, William; Golby, Christopher; Hamerlik, Petra; Karabatsou, Tina; Bailey, Matthew; D'Urso, Pietro; Djoukhadar, Ibrahim; Akkari, Leila; Richardson, Jenny; et al.
Abstract: OBJECTIVE: The Preoperative Brain Irradiation in Glioblastoma (POBIG) study evaluates for the first time the safety, feasibility, and impact of single fraction preoperative radiotherapy in newly diagnosed glioblastoma patients. METHODS: Operable patients with a radiological diagnosis of glioblastoma, by consensus of a multidisciplinary tumor board including two dedicated neuro-radiologists, are screened for the study. Anatomical and functional MRI sequences are acquired for further tumor characterization and preoperative radiotherapy planning. Radiotherapy is delivered approximately two weeks after the initial screening. Radiation targets the macroscopic and microscopic tumor region at risk of being left behind during surgery and spares at least 2cc tumor volume being debulked to safeguard unperturbed and clinically relevant tissue examination and molecular profiling. The study dose-escalates (from 8Gy to 14Gy) based on the time-to-event Continual Reassessment Methodology. Subsequently, patients undergo surgical debulking followed by postoperative fractionated radiotherapy 60Gy/30fr with concurrent temozolomide. RESULTS: The first POBIG study patient underwent preoperative radiotherapy followed by a subtotal resection of a left posterior fronto-opercular tumor and completed the postoperative chemoradiotherapy. Screening, study consent, MRI imaging and analysis, radiotherapy planning and delivery until surgery can be achieved within three weeks from screening while maintaining adequate and personalized patient communication. There were no surgical or radiotherapy delays or complications. During surgery, we successfully sampled unirradiated and irradiated tumor regions. The radiotherapy field covered the whole remnant tumor, and image-guided obtained tumor samples and imaging analysis showed clear evidence of differential radiation-induced changes. CONCLUSION: We successfully initiated a new treatment strategy of preoperative radiotherapy for glioblastoma patients. The first patient completed the treatment, and the study is now open for further recruitment. Paired tumor sampling and advanced imaging analysis showed promising results. The POBIG study offers a unique opportunity for a paradigm shift towards personalized treatment regimens, hopefully leading to better outcomes.